If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(7a+3)-(a+5)=-16
We simplify the equation to the form, which is simple to understand
(7a+3)-(a+5)=-16
Remove unnecessary parentheses
7a+3-(a+5)=-16
Remove unnecessary parentheses
7a+3-1a-5=-16
We move all terms containing a to the left and all other terms to the right.
+7a-1a=-16-3+5
We simplify left and right side of the equation.
+6a=-14
We divide both sides of the equation by 6 to get a.
a=-2.33333333333
| 3(5cx+y)=14cx-6y | | x+(x+2)+(x+4)+(x+6)+(x+8)=30 | | 25=y-50 | | x/9+5-6 | | 0.30(30)+0.15x=0.20(30+x) | | 5x-0.8=6x | | 12+p=16 | | (x-3/4)-(x+5/6)=(5x-3/9) | | 5(x-3)-2(x+6)=30 | | 18=p+3 | | 7x+x-4=7x+5 | | 4(y-6)/3 | | 23=n-5 | | 7(m-1)-3(5m+2)=-9(m+3)-10 | | -3x-(-7)=-1 | | 0.32=w-0.1 | | 4[1-(-5x-7)]=100x+144 | | -2(w-4)-(4+6w)=-9w | | .09x^2+.03=.21 | | 3x-(x+6)=-4(x+1) | | .3y+.5=.42 | | 44/4 | | 44/11 | | 36n^3=49n | | 3-4(4m-7)=-17 | | X+(3/4)=(-9/2) | | 3x^2+52x+12=0 | | 8x+9=6x+39 | | 8(x-6)=9+7x | | 22+20x=4x | | 5(0)-7x=-7(5+x) | | 7z+7-5z=9+z-3 |